2018
DOI: 10.1002/cctc.201801089
|View full text |Cite
|
Sign up to set email alerts
|

Design of Ordered Mesoporous Sulfonic Acid Functionalized ZrO2/organosilica Bifunctional Catalysts for Direct Catalytic Conversion of Glucose to Ethyl Levulinate

Abstract: Ordered mesoporous sulfonic acid functionalized ZrO 2 /organosilica catalysts (SO 4 2À /ZrO 2 -PMO-SO 3 H) bearing tunable Brønsted, and Lewis acid site distributions were prepared by a P123directed sol-gel co-condensation route followed by ClSO 3 H functionalization. As-prepared catalysts were applied in the conversion of glucose to ethyl levulinate in ethanol medium. The SO 4 2À /ZrO 2 -PMO-SO 3 H-catalyzed target reaction followed a glucose-ethyl glucoside-ethyl fructoside-5-ethoxymethylfurfuralethyl levuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The Zr 3d and S 2p appears for UiO‐66‐SO 3 H‐NH 2 (Figure A‐c); the S 2p spectrum in Figure D consists of two peaks at 169.8 and 168.6 eV, which are identified as the S 2p 1/2 and S 2p 3/2 binding energy . Figure E shows the peak of Zr 3d at the binding energy of 185.7 and 183.3 eV, which correspond to Zr3d 3/2 and Zr 3d 5/2 . By analyzing the XPS high‐resolution spectrum of Zr 3d and S 2p, it can be further concluded that the UiO‐66‐SO 3 H‐NH 2 /PDA@GO are successfully synthesized in this study, which was consistent with the aforementioned FT‐IR test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zr 3d and S 2p appears for UiO‐66‐SO 3 H‐NH 2 (Figure A‐c); the S 2p spectrum in Figure D consists of two peaks at 169.8 and 168.6 eV, which are identified as the S 2p 1/2 and S 2p 3/2 binding energy . Figure E shows the peak of Zr 3d at the binding energy of 185.7 and 183.3 eV, which correspond to Zr3d 3/2 and Zr 3d 5/2 . By analyzing the XPS high‐resolution spectrum of Zr 3d and S 2p, it can be further concluded that the UiO‐66‐SO 3 H‐NH 2 /PDA@GO are successfully synthesized in this study, which was consistent with the aforementioned FT‐IR test.…”
Section: Resultsmentioning
confidence: 99%
“…For the past few years, due to the use of a large number of nonrenewable fossil energy, people are faced with a major challenge from declining petroleum supplies and the environmental pollution . Thus, it is of great significance to study the production of available chemicals and valuable biofuels from a wide, cheap, and renewable biomass to replace traditional fossil energy .…”
Section: Introductionmentioning
confidence: 99%
“…TG (5.8 nm), to penetrate into the pore channels and contact the active sites Wu et al, 2014a). Sol-gel, polymeric precursor, microwave and hydrothermal are some of the critical synthetic processes for fabricating mesoporous materials (Song et al, 2018;Soltani et al, 2017;Xie et al, 2016). Mesostructured nano-catalysts can be prepared via post-synthesis procedure such as grafting methods and direct synthesis like cocondensation reactions.…”
Section: Development Of Mesoporous Nano-catalystsmentioning
confidence: 99%
“…The cascade proceeds via glucose-ethyl glucoside-ethyl fructoside-5-ethoxymethylfurfural-ethyl levulinate, in which Bronsted acidity is required for the etherification and dehydration steps, while Lewis acidity promotes isomerization pathways. Hydrophobic PMO-based catalysts were found to be less susceptible to deactivation owing to inhibition of water byproduct adsorption [133].…”
Section: Sulfonic-acid-functionalized Pmosmentioning
confidence: 99%